Securing Water Quality and Motor Functionality with IoT Borewell Monitoring - Kumar Yegireddy, Narendra; M, N V S S Kumar; Santosh Kumar, Gottapu; G. , Prasanthi (International Journal of Psychosocial Rehabilitation, 2020)
Due to the rising population and excessive water usage, groundwater levels have declined. Inconsistent rainfall patterns and monsoon failures have forced many people to rely on groundwater, leading them to drill wells for their water supply. Unfortunately, water quality is affected negatively by both natural factors and human activities, including improper waste disposal in landfills. This not only affects water quality but also damages farmland. However, technological advancements such as IoT (Internet of Things), cloud computing, big data, and web-based tools have made it possible to address these significant challenges. These include issues related to poor drinking water quality, increased labor demands, and motor damage due to insufficient monitoring. To tackle these challenges, we have implemented a project that monitors water quality and motor parameters to prevent motor breakdown. The system incorporates two sensors: a pH sensor for assessing water quality and an ultrasonic sensor for measuring water level and temperature. Additionally, a current sensor is employed to monitor the motor’s performance. A single microcontroller chip collects data from these sensors, while a Wi-Fi chip transmits this information from a borewell to the cloud. If the data related to water quality and motor performance deviates from the preset thresholds established in the code, this information is relayed to a mobile application accessible to individuals in the area. This system provides a convenient means to remotely monitor various borewell parameters through a mobile application.